Iron pill associated duodenitis: a less recognised clinical entity - Guha, Jayjit; Taneja, Vinus; Khosla, Pooja; Dessai, Rishikesh; Sondhi, Manuj (International Journal of Research in Medical Sciences, 2024)
Iron supplementation is a widely prescribed treatment for anemia, but its association with gastrointestinal complications, specifically duodenitis, remains inadequately acknowledged in clinical practice. One of the common oral iron preparations to treat iron deficiency anemia is ferrous sulphate. Iron preparations have been known to cause gastric side effects, including gastritis and duodenitis. This case report explores the emerging concern of iron pill-associated duodenitis, shedding light on the potential adverse effects of oral iron supplementation on the duodenal mucosa. Existing literature and clinical cases are reviewed to highlight the connection between iron pill consumption and duodenal inflammation. From asymptomatic cases to severe symptoms like abdominal pain and gastrointestinal bleeding, the clinical spectrum is diverse. Histopathological analysis of endoscopic biopsies reveals characteristic features of duodenitis linked with iron deposits, raising concerns about long-term consequences. In conclusion, this case underscores the significance of recognizing iron pill-associated duodenitis as a distinct clinical entity, necessitating further investigation for optimized patient care and the safe administration of iron supplements in managing anemia.